Hypotonia and delayed motor development as an early presentation of Lowe syndrome: case report and literature review. Issue 6 (2nd November 2019) - David, Sara; De Waele, Kathleen; De Wilde, Bram; Faes, Franny; Vanakker, Olivier; Walraedt, Sophie; Prytuła, Agnieszka
ABSTRACT: We describe a boy who presented with neonatal hypotonia, followed by delayed motor development and growth impairment. Further evaluation revealed rickets caused by proximal renal tubular dysfunction. At age 3, the boy exhibited dysmorphic features and bilateral cataract. Genetic analysis of the OCRL gene showed a novel variant in exon 13: c.1250T>A, p.Val417Asp; in silico and segregation analysis confirmed the variant to be pathogenic, compatible with the diagnosis of the oculocerebrorenal syndrome of Lowe. Lowe syndrome is a rare multisystemic disorder; the diagnostic triad requires involvement of the eye, central nervous system and the proximal renal tubule. Typical clinical features are congenital cataract, glaucoma, hypotonia, mental and behavioral problems, benign skin lesions, platelet dysfunction and dental abnormalities. Phenotypic features early in life may be nonspecific, which is illustrated by this case with a late manifestation of cataract. Because an early diagnosis can lead to better counseling and treatment, we suggest urinary testing for proteinuria as a part of the evaluation of children with unexplained hypotonia.